(untitled) (Argos, 2025)
This article sets out to tackle the constructive function of the fold, the contradiction and the inversion in Euripides’ Alcestis. To this end, it defines the main terms under consideration, explores the tragedy in search of their manifestations, and indicates why the manifold contradictory elements present in the play, far from being distractions, underline the complexity of Euripides’ ideological and narrative universe.